A technical note on the decision of sending remittances: An overlapping generations model on the self-interest motive of remittances - Cabuay, Christopher James R. (Animo Repository, 2012)
The motivations to remit may be summarized into altruism and self-interest, which is composed of exchange, strategic, insurance and investment motives. Under self-interest, migrants remit so as to maximize income across time. By devising an unconventional overlapping generations model elaborating on the migrant's decision to remit, this paper draws three key findings. The amount a migrant remits increases with his level of income, given that he has a positive time preference. The level of remittances increases with the gross rate of return if the migrant is risk neutral or relatively less risk averse. Lastly, the level of remittances decreases with the depreciation of exchange rates. Copyright © 2012 De La Salle University, Philippines.